Low Uptake of Antiretroviral Therapy and High Mortality After Tuberculosis or Opportunistic Infection in KwaZulu-Natal, South Africa - Murphy, Richard A. (2010)
OBJECTIVES: A prospective cohort study was conducted among HIV-infected inpatients with tuberculosis or other opportunistic infection (OI) in South Africa to estimate subsequent antiretroviral therapy (ART) uptake and survival. METHODS: Logistic regression modeling explored associations between baseline characteristics and starting ART, and ART exposure adjusted incidence of death was estimated over 6 months of follow-up. RESULTS: Among 49 participants enrolled, median CD4 cell count at hospital discharge was 42 cells/mm(3), and the most common presenting OI were tuberculosis (76 %), Pneumocystis pneumonia (8%), chronic diarrhea (8%), cryptococcal meningitis (6%), and Toxoplasmosis gondii (4%). By 6 months, only 20 (45%)had initiated ART, and 4 (8%) were lost to follow-up. ART uptake was independently associated with previous use of traditional medicine (OR 7.2; 95% CI 1.4 – 55.1) and with less advanced HIV infection (baseline CD4 count (per 50 cells/mm(3)increase OR 1.4; 95% CI 0.9–2.2). A total of 14 (31%)died before initiating ART; the monthly incidence of death did not decrease over the 6 month interval. CONCLUSION: High mortality observed within the 6 months following hospitalization with tuberculosis or other acute OI argue that mechanisms are needed to expedite ART for patients after AIDS-defining illness.